2021
DOI: 10.1007/s40747-021-00406-w
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for multicriteria decision-making based on the hesitant fuzzy best–worst method

Abstract: Hesitant fuzzy preference relations (HFPRs) have been widely applied in multicriteria decision-making (MCDM) for their ability to efficiently express hesitant information. To address the situation where HFPRs are necessary, this paper develops several decision-making models integrating HFPRs with the best worst method (BWM). First, consistency measures from the perspectives of additive/multiplicative consistent hesitant fuzzy best worst preference relations (HFBWPRs) are introduced. Second, several decision-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…Ref. [27] introduced a framework for the MCDM process based on the indecisive fuzzy BWM and verified the feasibility and validity of the model. Ref.…”
Section: The Best-worst Methodsmentioning
confidence: 93%
“…Ref. [27] introduced a framework for the MCDM process based on the indecisive fuzzy BWM and verified the feasibility and validity of the model. Ref.…”
Section: The Best-worst Methodsmentioning
confidence: 93%
“…Because of its excellent performance, BWM is quickly accepted and adopted in many decision-making problems (Amiri et al 2020). In view of the potential of BWM to deal with DM weights in some cases (Li et al 2021b), we expand BWM in this study to obtain DM weights, shown as Fig. 1.…”
Section: The Methods To Determine the Dm Weights Based On Bwmmentioning
confidence: 99%
“…In addition, COPRAS is able to delineate the ratios simultaneously to both ideal and worst solutions. Owing to its advantages, several researchers have employed the COPRAS approach for different purposes [ 16 , 46 , 54 ]. As MCDM problems have become increasingly complex and uncertain, different researchers have extended the conventional COPRAS approach to a variety of uncertain environments.…”
Section: Literature Reviewmentioning
confidence: 99%